2012
DOI: 10.3126/jonmc.v1i1.7288
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of maternal health care services in Belbari VDC of Eastern Region of Nepal

Abstract: Background: Appropriate utilization of maternal health care services is very important to reduce the maternal morbidity and mortality rate in the country and healthful practices while caring mother is needed to improve the health condition of both mother and child. Objectives: Main objectives of this study is to assess the utilization of Maternal health care services and know the cultural practices about care of mother and children of under one year of children. Methodology: Descriptive cross sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…It reflects u liza on of ins tu onal delivery services is remarkable in our study area, this difference may be due to different geographical pa erns and facili es available in two se ngs, as our study area is in outskirts of capital city of Nepal. Likewise, more than 90% had done their four-me antenatal checkup which was assessed based on WHO recommenda on and almost all got Tetanus Toxoid injec on and Albendazole in their last pregnancy among our study par cipants which is similar with the findings of study 15 of eastern part of Nepal. In contrast to this, one third of 13 women did not go for ANC in Jumla.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It reflects u liza on of ins tu onal delivery services is remarkable in our study area, this difference may be due to different geographical pa erns and facili es available in two se ngs, as our study area is in outskirts of capital city of Nepal. Likewise, more than 90% had done their four-me antenatal checkup which was assessed based on WHO recommenda on and almost all got Tetanus Toxoid injec on and Albendazole in their last pregnancy among our study par cipants which is similar with the findings of study 15 of eastern part of Nepal. In contrast to this, one third of 13 women did not go for ANC in Jumla.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, our study showed that 94.5% of women of under one year age children had delivered in hospital and only 5.4% had home delivery which is approximately similar to the study conducted in eastern part of Nepal, where 80% had 15 ins tu onal delivery and 20% had home delivery. On contrary to this, in Jumla 95.8% women had given their child 14 birth at home.…”
Section: Discussionsupporting
confidence: 67%
“…26 Findings from Belbari village of Nepal show that 40% children got solid food before six months and rest 60% got after six months of age. 27 The prevalence of timely initiation of complementary feeding was 60.5% in Ethiopia. 28 Dietary diversity on weaning foods varies from jaulo, daalbhat to cows/buffalo/packet milk, vegetables, fruits (banana, apple), meat/egg/paneer, similar to the study from Bombay slums.…”
Section: Discussionmentioning
confidence: 99%
“…6 But visit for antenatal checkup in the government hospital was found to be more (52%) than private service (48%) in a study done in Eastern Nepal. 12 The reason for more antenatal checkups in government health centers and hospitals might be because of free services and medications provided to the client along with the incentive package of safe motherhood programs. Annual health 2069/70 reports 71.4 percentage of population were found utilizing free health care services among total reported morbidity.…”
Section: Government/privatementioning
confidence: 99%